Legal authorized representative experience with smartphone-based electronic informed consent in an acute stroke trial. (17th September 2019) - Haussen, Diogo C; Craft, Leah; Doppelheuer, Shannon; Rodrigues, Gabriel Martins; Al-Bayati, Alhamza R; Ravindran, Krishnan; Schultz, Meagan; Sutherly, Loretta; Schindler, Kiva M; Frankel, Michael R; Nogueira, Raul G
Abstract : Background: The pilot use of a smartphone platform for electronic informed consent (e-Consent) in large vessel occlusion acute stroke (LVOS) trials has recently been reported. The degree of satisfaction from Legal Authorized Representatives (LARs) with regard to this process remains to be established. Methods: A single-center study evaluating the experience of LARs with the use of e-Consent in a LVOS randomized trial of an investigational drug administered within 12 hours of last known normal was carried out. A structured survey was used to evaluate the experience of the LARs with the e-consenting process. Results: From February to November 2018, 60 consecutive patients were e-Consented. Of these, 53 LARs completed the survey. The median (IQR) age of the patients was 63 (53–70) years, baseline/discharge National Institutes of Health Stroke Scale score was 17 (12–20)/3(1–12), and 45% were independent at discharge. The survey was applied in person in 43% of cases and via telephone in 57%. Median LAR age was 48 (39–59) years, 64% were female, and a multi-ethnic composition was observed. Forty percent of LARs had less than tertiary level of education (high-school or less). Regarding the e-Consent, 98% of LARs reported to be 'clear' and 83% felt 'very comfortable' in signing. The overall experience was 'excellent/good' in 91%. Despite the positive general impression regarding the use of e-Consent, 12 LARs (22%) would have preferred paper consent. Multivariable regression indicated that lower educational status (tertiary education or less: OR 5.09, 95% CI 1.02 to 25.48; p=0.04) and lower baseline ASPECTS score (OR 0.63, 95% CI 0.41 to 0.96; p=0.03) were independently associated with preference for paper consent. Conclusions: e-Consent was overall very well perceived by LARs in a randomized clinical trial of LVOS. A minority of proxies, who were more commonly less formally educated, would have preferred paper consenting.